2018
DOI: 10.1021/acssuschemeng.7b02711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemically Synthesized SnS Nanocrystals: Impact of Nonstoichiometry on Phase Purity and Solar Cell Performance

Abstract: We demonstrate nontoxic, earth-abundant lightabsorbing SnS thin films fabricated by a low-cost, environmentally friendly nonvacuum process. SnS nanocrystals (NCs) are mechanochemically synthesized from elemental powders without the use of any other additives or solvents. To investigate the effect of the Sn-to-S stoichiometric ratio on the crystalline phase of the SnS NCs, the nonstoichiometry is systematically controlled from 0.95 (Sn 0.95 S) to 1.05 (Sn 1.05 S) by adjusting the mixing ratio of the Sn and S po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…To overcome this, Steinmann et al reported that annealing SnS for 1 h under vacuum conditions (15 m Torr) at 500 °C or in an Ar or H 2 gas atmosphere at ambient temperature prevents the formation of impurity phases . Moreover, introducing Sn excess composition (Sn 1.05 S) during the synthesis process significantly reduces the formation of Sn 2 S 3 without additional thermal processing . In summary, the methods and strategies proposed have the potential to significantly benefit the PV community by enabling them to fabricate highly efficient BaZrS 3 -based devices as technology advances.…”
Section: Comparison Of Scaps-1d Results With Bazrs3 and Ba(zrti)s3 Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this, Steinmann et al reported that annealing SnS for 1 h under vacuum conditions (15 m Torr) at 500 °C or in an Ar or H 2 gas atmosphere at ambient temperature prevents the formation of impurity phases . Moreover, introducing Sn excess composition (Sn 1.05 S) during the synthesis process significantly reduces the formation of Sn 2 S 3 without additional thermal processing . In summary, the methods and strategies proposed have the potential to significantly benefit the PV community by enabling them to fabricate highly efficient BaZrS 3 -based devices as technology advances.…”
Section: Comparison Of Scaps-1d Results With Bazrs3 and Ba(zrti)s3 Ch...mentioning
confidence: 99%
“… 110 Moreover, introducing Sn excess composition (Sn 1.05 S) during the synthesis process significantly reduces the formation of Sn 2 S 3 without additional thermal processing. 111 In summary, the methods and strategies proposed have the potential to significantly benefit the PV community by enabling them to fabricate highly efficient BaZrS 3 -based devices as technology advances.…”
Section: Comparison Of Scaps-1d Results With Bazrs 3 ...mentioning
confidence: 99%
“…For insoluble compounds, which cannot be deposited from a solution, spin coating from suspensions is a viable alternative. This has been demonstrated for the construction of solar cells, using SnS 51 or Cu(In,Ga)Se 2 , 52 and requires the optimization of the suspension used for spin coating by exploring the use of ultrasonication or wet milling to improve the dispersion of the solid into the suspension. This work is beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Park et al synthesized SnS nanocrystals by planetary ball milling method and explored their performance and application as thin film solar cells. 31 These traditional ball milling methods have been studied and applied in the preparation of metal sulfides, but the conversion rate of sulfide prepared from simple substances is not high and the preparation process takes a long time due to the limitation of the grinding medium and grinding equipment.…”
Section: Introductionmentioning
confidence: 99%